A Visible Energy Management by Photochromic Solar Thermal Fuel Using a Color Display. Issue 12 (20th October 2020) - Fei, Liang; Yin, Yunjie; Zhang, Jinju; Wang, Chaoxia
Abstract : Photocontrolled solar thermal fuel offers enormous potential for light harvesting, storage, and thermal management. Monitoring energy storage process still remains significantly challenging with an evident and convenient display. Inspired by the battery indicator on the phone with color variation, a visible solar thermal fuel (VSTF) is designed by compositing photochromic azobenzene with organic phase change materials. This is an efficient strategy for improving renewable energy storage capacity without solvent assistance, and displaying the energy storage process. The photochromic dopant enables color change due to varying light‐absorption wavelengths with the conformational change. Notably, the energy release situation of charged composite under sunlight stimuli is demonstrated to heat water, showing about 4 °C higher than that of the uncharged one. The color difference depends on the isomerization extent ( trans %) which links to the energy storage parameters. It has potential to display the energy storage process and utilize the energy more efficiently. Abstract : A visible solar thermal fuel is designed to monitor the renewable energy storage process during charging or discharging, contributing to utilizing the energy more efficiently for human energy management. Color change can be a signal to record the isomer extent by a photochromic molecule, showing the energy storage parameters at real‐time monitoring, such as energy density and crystallization/melting point.